THE FACTORS AFFECTING THE SATISFACTION OF THE SERVICE USERS AT PERTIWI MOTHER AND CHILD RSKD - sitti zaenab (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2018)
This research aimed to investigate the effect of the service quality, facilities, and location on the satisfaction of the service users at Pertiwi Mother and Child RSKD. The research used the Regression Equation. The objects researched on were the 160 users of Pertiwi Mother and Child RSKD, who were chosen using the incidental sampling technique. The data were collected using the technique of distributing questionnaires to the patients as the users of the services at Pertiwi Mother and Child RSKD. The research results indicated that the service quality, tariff, facilities and location had a positive and significant effect on the satisfaction of the service users.